Diagnostic value of mid-regional pro-Adrenomedullin as a biomarker of invasive bacterial infection in children: a systematic review - Michael Paul Corr; Derek Fairley; James P. McKenna; Michael D. Shields; Thomas Waterfield (BMC, 2022)
Abstract Background Invasive bacterial infections (IBI) in children present a difficult clinical challenge. They are often life-threatening, however in the early stages they can be hard to differentiate from benign viral infections. This leaves clinicians with the risk of missing a serious IBI diagnosis or inappropriately using antimicrobials in a child with a viral infection- contributing to the ongoing development of increased antimicrobial resistance. Hence, biomarkers which could aid in early detection of IBI and differentiation from viral infections are desirable. Mid-Regional pro-Adrenomedullin (MR-proADM) is a biomarker which has been associated with IBI. The aim of this systematic review was to determine its diagnostic accuracy in identifying children with IBI. Methods A strategy was devised to search online databases MEDLINE, Embase, Web of Science and Scopus for human clinical trials reporting the accuracy of MR-proADM in children. Against predesigned inclusion and exclusion criteria full texts were selected for inclusion and data extraction. True positives, false positives, true negatives and false negatives were extracted from each included study to fill 2 × 2 tables. Using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool methodological quality of each study was assessed. Results A total of 501 articles were initially identified. After the removal of duplicates and abstract screening 11 texts were fully reviewed and four texts (totaling 1404 patients) were included in the systematic analysis. Only one study was of a high quality and that study accounted for the vast majority of patients. A single study reported the diagnostic accuracy of MR-proADM for invasive bacterial infection reporting an Area under the Curve of 0.69. The paucity of available studies made meta-analysis and studies of heterogeneity impossible. Conclusion There is a paucity of research regarding the diagnostic accuracy of MR-proADM in the diagnosis of invasive bacterial infections in children. Initial results would suggest that MR-proADM testing alone is poor at identifying IBI in young children. It remains unclear if MR-proADM performs differently in older children or in children with signs and symptoms of IBI. Trial registration PROSPERO CRD42018096295 .